Amperometric detection of extended-spectrum β-lactamase activity: application to the characterization of resistant E. coli strains. Issue 10 (21st May 2015) - Rochelet, Murielle; Solanas, Sébastien; Betelli, Laetitia; Neuwirth, Catherine; Vienney, Fabienne; Hartmann, Alain
<x xml:space="preserve">Abstract</x> Rapid electrochemical detection of extended-spectrum β-lactamase producing strains.